2019
DOI: 10.1017/brimp.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences and needs of homeless aboriginal and torres strait islander peoples with neurocognitive disability

Abstract: Objective:The current study explored the experiences and aspirations of a cohort of Aboriginal and Torres Strait Islander adults with neurocognitive disability residing in a homeless shelter in regional Queensland, Australia. Neurocognitive disability (NCD) refers to any acquired disorder or injury to the brain where the primary clinical deficit is in cognitive function.Method:The data reported on in this paper emerged from a broader study that aimed to understand the extent and nature of neurocognitive disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Holistic, empowering approaches, which recognise and respond to the specific needs of homeless Aboriginal and Torres Strait Islander people, are required (Memmott et al, 2012). It is vital that services acknowledge and understand Indigenous concepts of disability and the impact of trauma; recognise the impact of the past on Aboriginal and Torres Strait Islander peoples' access and engagement with services; and utilise culturally safe and appropriate screening processes which accurately assess cognitive and psychosocial needs (Townsend et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holistic, empowering approaches, which recognise and respond to the specific needs of homeless Aboriginal and Torres Strait Islander people, are required (Memmott et al, 2012). It is vital that services acknowledge and understand Indigenous concepts of disability and the impact of trauma; recognise the impact of the past on Aboriginal and Torres Strait Islander peoples' access and engagement with services; and utilise culturally safe and appropriate screening processes which accurately assess cognitive and psychosocial needs (Townsend et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Although limited, research suggests that many marginalised Indigenous Australians experience complex multiple problems including NCD, FASD, intellectual disability and mental health problems (Massey, Jane, Lindop, & Christian, 2013;Stephens, Cullen, Massey, & Bohanna, 2014;Townsend et al, 2017a). The nature and extent of NCD among homeless Aboriginal and Torres Strait Islander young people is unclear, but is thought to be reflective of the adult population, and therefore likely to be high.…”
Section: Homeless Aboriginal and Torres Strait Islander Young People mentioning
confidence: 99%
“…There is a critical gap in understanding what could lead to improvements in care, support and housing and inform intervention for older people experiencing memory problems and homelessness. Although studies have explored the lived experiences of older people experiencing homelessness [ 26 ], we found only one Australian study which privileged the voices of people living with memory problems and experiencing homelessness, through in-depth qualitative interviews, and this was in a single hostel and did not focus on older people [ 27 ]. Qualitative and ethnographic studies are increasingly being conducted to inform practice, intervention development and policy in homelessness [ 19 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Blaxland et al (2020) found that only 4% and 7% of people with ABI and stroke respectively self managed their NDIS plans while only 8% and 13% respectively were partially managing their plans. These issues may be more challenging for those with recent ABI (Foster et al, 2012;Zasler, Ameis & Riddick-Grisham, 2013), those from Aboriginal or Torres Strait Islander backgrounds (Stephens, Cullen, Massey & Bohanna, 2014;Townsend et al, 2018) and those with socio-economic disadvantage (Cortese et al, 2021). They may further be complicated where individuals with ABI have little family support (Cortese et al, 2021) or where transitions are required between existing insurance or disability services (Esterman et al, 2018;Lakhani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%